1990
DOI: 10.1002/ana.410270414
|View full text |Cite
|
Sign up to set email alerts
|

Normal pressure hydrocephalus associated with cauda equina neurinoma

Abstract: A 65-year-old woman with normal pressure hydrocephalus experienced improved gait and hydrocephalus following surgical resection of a cauda equina neurinoma. Fibrinogen, detected in the cerebrospinal fluid, may be involved in the pathophysiological process of normal pressure hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Higher levels of thrombopoietin [34], ferritin [35], nerve growth factor[36], chondroitin sulfate proteoglycan [37] transforming growth factor β1 [38,39], transforming growth factor β2 [37], S-100 protein [40,41], and vascular endothelial growth factor [42] have been found in ventricular CSF in patients with hydrocephalus resulting from intraventricular hemorrhage. Even in patients without any intraventricular blood, elevated proteins have been found in ventricular CSF in hydrocephalus resulting from intracranial schwannomas [7], a few cases of spinal schwannomas [8,9], and in about 4% of patients with Guillain-Barre' syndrome [10,11]. In a review of potential biomarkers for chronic hydrocephalus, Tarnaris et al concluded that tumor necrosis factor, tau protein, lactate, sulfatide and neurofilament triple protein are elevated in chronic hydrocephalus to make them the most promising CSF markers [43].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of thrombopoietin [34], ferritin [35], nerve growth factor[36], chondroitin sulfate proteoglycan [37] transforming growth factor β1 [38,39], transforming growth factor β2 [37], S-100 protein [40,41], and vascular endothelial growth factor [42] have been found in ventricular CSF in patients with hydrocephalus resulting from intraventricular hemorrhage. Even in patients without any intraventricular blood, elevated proteins have been found in ventricular CSF in hydrocephalus resulting from intracranial schwannomas [7], a few cases of spinal schwannomas [8,9], and in about 4% of patients with Guillain-Barre' syndrome [10,11]. In a review of potential biomarkers for chronic hydrocephalus, Tarnaris et al concluded that tumor necrosis factor, tau protein, lactate, sulfatide and neurofilament triple protein are elevated in chronic hydrocephalus to make them the most promising CSF markers [43].…”
Section: Discussionmentioning
confidence: 99%
“…Because the CSF protein level of our patient was elevated, his characteristics are more reminiscent of sNPH. Previous reports show that spinal cord tumors can be associated with NPH [4][5][6][7][8][9]. Hyperviscosity in cases with elevated CSF proteins produced by spinal cord tumors may cause obstructive hydrocephalus.…”
Section: Discussionmentioning
confidence: 97%
“…We summarized the previously reported cases of neurinoma with hydrocephalus in Table 1 [4][5][7][8][9][10]. Middle-age, female gender, and high CSF protein levels are risk factors of sNPH with spinal neurinoma.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 High CSF fibrinogen concentration in patients with glioma or spinal cord tumors was also considered a cause of hydrocephalus. 26,27 Several other mechanisms might be correlated to nonobstructive hydrocephalus development. Finally, we could not perform surgical removal as an initial treatment because of poor general condition, and VP shunt occlusion remains a possibility.…”
Section: Discussionmentioning
confidence: 99%